Cortical malformations and COL4A1 mutation: Three new cases. (May 2019) - ,; Accorsi, P.; Battaglia, D.; Cereda, C.; Martelli, P.; Mine, M.; Pinelli, L.; Tartaglione, T.; Ghi, T.; Parrini, E.; Zuffardi, O.; Vitale, G.; et al.
Abstract: Aim: The COL4A1 gene (13q34) encodes the α1 chain of type IV collagen, a crucial component of the basal membrane. COL4A1 mutations have been identified as a cause of a multisystem disease. Brain MRI in COL4A1 -mutated patients typically shows vascular abnormalities and white matter lesions. Cortical malformations (specifically schizencephaly) have also recently been described in these patients, suggesting that these, too, could be part of the phenotypic spectrum of COL4A1 mutations. The aim of our work was to retrospectively evaluate COL4A1 -mutated subjects diagnosed at our centers in order to assess the frequency and define the type of cortical malformations encountered in these individuals. Method: We retrospectively reviewed MRI data of 18 carriers of COL4A1 mutations diagnosed in our centers between 2010 and 2016. Results: We identified polymicrogyria in two patients, and schizencephaly in the mother of a further patient. Interpretation: Our findings confirm that cortical malformations should be considered to fall within the phenotypic spectrum of COL4A1 mutations and show that not only schizencephaly but also polymicrogyria can also be found in mutated individuals. Although further studies are needed to clarify the underlying pathogenetic mechanism, independently of this, the timing of the brain damage could be the crucial factor determining the type of lesion. Highlights: The phenotypic spectrum of COL4A1 mutations includes cortical malformations. Polimicrogyria/schizencephaly, should be taken into account. An acquired encephaloclastic defect mechanism seems most likely. The lesion type probably depends mainly on the damage timing.